Bacterial multi-resistance to antibiotics in water from plant cavities (phytotelms) in a deep tropical forest from Costa Rica - Sánchez-Vargas, Stephanny (2023)
Introduction: The spread of antimicrobial resistance in natural environments continues to be reported throughout the world; nevertheless, there is no study about phytotelms (water in the natural cavities of plants) in the deep understory of tropical cloud forests from Costa Rica. Objective: To detect phytotelm antibiotic-resistant bacterial strains in a Costa Rican forest and nearby town. Methods: We used the disk diffusion method to analyze the antimicrobial resistance of 10 gram-negative bacterial strains from phytotelm water collected from 10 bromeliads and 10 heliconias in both sites. Results: Three strains were multidrug resistant to more than three antibiotics in each site, and only one strain was susceptible to all antibiotics. Antibiotic resistance was similar in both environments. Conclusions: Phytotelm can be a rapid, cost-effective, and simple source for detecting antimicrobial resistance in unexplored environments.